Comparing Islam with other Late Antique Religions: Examining Theological Parallels with Zoroastrianism, Judaism, Christianity, and Manichaeism - Nakissa, Aria (Universitas Islam Internasional Indonesia, 2023)
This article argues that Islamic theological doctrines emerged out of broad late antique religious trends. Such trends were reflected in Judaism and Christianity, but also transcended them. In support of this view, the article systematically examines parallels between Islamic theological doctrines, and those found in the late antique religions of Zoroastrianism, Judaism, Christianity, and Manichaeism. It is argued that all of these religions share six basic doctrines: (1) belief in one morally-concerned Supreme Being (2) belief in lesser spirit beings that are good or bad (3) belief in prophets (4) belief in scriptural texts (5) belief in an afterlife (6) belief that the world will end with the triumph of good over evil. It is argued that the preceding six doctrines coherently fit together into a larger perspective on the universe. The article explains how this perspective is central to late antique religions, including Islam.